Agent-based fault tolerant framework for manufacturing process automation. Issue 3 (4th March 2019) - Khan, Zubair Ahmad; Khan, Muhammad Tahir; Ul Haq, Izhar; Shah, Kamran
ABSTRACT: Disruption in manufacturing process adversely affects the productivity, efficiency and increases the downtime, which severely affects the consumer-centric value. In this regard, it is inevitable to bring about disruption in an effective way. Agent-based techniques are frequently practised to deal with multiple industrial-based disruptions regarding handling machine faults. This current research work is an endeavour to mitigate disruption by deploying Agent-Based Fault Tolerant Framework (ABFTF) in the manufacturing process; this technique is adept to handle Fault Detection and Identification (FDI) effectively, as well as it responds to the disruption dynamically to assess the root cause. Once disruption is identified, weight is assigned to it in a pre-defined manner and a corrective mechanism is executed. This proposed model was implemented on asphalt manufacturing plant. The observed reduction in downtime was 80.26 min in 24 h, while the overall production was improved by 5.1%, casting worthwhile impacts on process efficiency and consumer-centric value in comparison to established logics.